On the Shallow Processing (Dis)Advantage: Grammar and Economy - Koornneef, Arnout; Reuland, Eric (Frontiers in Psychology, 2016)
In the psycholinguistic literature it has been proposed that readers and listeners often adopt a ‘good-enough’ processing strategy in which a ‘shallow’ representation of an utterance driven by (top-down) extra-grammatical processes has a processing advantage over a ‘deep’ (bottom-up) grammatically-driven representation of that same utterance. In the current contribution we claim, both on theoretical and experimental grounds, that this proposal is overly simplistic. Most importantly, in the domain of anaphora there is now an accumulating body of evidence showing that the anaphoric dependencies between (reflexive) pronominals and their antecedents are subject to an economy hierarchy. In this economy hierarchy, deriving anaphoric dependencies by deep – grammatical – operations requires less processing costs than doing so by shallow – extra-grammatical– operations. In addition, in case of ambiguity when both a shallow and a deep derivation are available to the parser, the latter is actually preferred. This, we argue, contradicts the basic assumptions of the shallow-deep dichotomy and, hence, a rethinking of the good-enough processing framework is warranted.